Peran BUMDesa dan LPM Batu Kumbung Dalam Membranding Desa Wisata - Muhammad Arfa; Fatimatuzzahra Fatimatuzzahra (Universitas Bumigora, 2021)
Batu Kumbung touism village is a tourism village that was established in 2019.The development is quite good towards an independent tourism village, data shows that interest in visiting in 2020 is quite good, local residents increase the improvement of alternative living standards. BUMDesa and LPM Foundation by increasing the potential value of each area in Batu Kumbung. This research applied descriptive qualitative, all of the data obtained from informantsh have a Snowball character (still have a general character), observation has been done by the researcher in Batu Kumbung village to find some informants. Furthermore, the researcher conducted in-depth interview by using a semi-structured formation. Then, all of the documents are needed as the data, obtained from BUMDES, LPM, and Cultural Institution which exist in the village. The analysis used Schlegel theory about the Grounded Research Process. The result of the research found some efforts namely: the branding of Batu Kumbung tourism village did not change the existing potential, all the potential thing which are exist in the village have been repackaged into precious thing. Utilizing existing potential and showing the uniqueness of the village of Batu Kumbung provides more value as the tourism object.